Consumer behavior toward virtual wine experiences as a technology-based sustainable transformation - Gastaldello, Giulia; Rossetto, Luca; Giampietri, Elisa (Frontiers in Sustainable Food Systems, 2024)
This study examines the behavior of wine consumers towards virtual wine experiences (VWEs), which are innovative and resilient solutions adopted by actors in the wine and wine tourism sectors during the recent pandemic, with an inherent potential for sustainability. While the phenomenon is still evolving due to the digitalization megatrend and the marketing potential of VWEs for wineries, the literature on this topic is still limited. We apply an extended Theory of Planned Behavior (TPB), relying on a large and representative sample of Italian wine consumers to analyze the effect of personal wine involvement, risk attitude, and future wine tourism intention in addition to attitude, subjective norms, and perceived behavioral control. The results confirm that attitude, subjective norms, perceived behavioral control, wine involvement, and future wine tourism intention positively influence intentions, while risk aversion negatively affects behavior. This first application of the TPB to technology-based wine experiences. It provides key insights for researchers, practitioners (such as wineries and wine tourism stakeholders), and policymakers for the development of VWEs.